Emerging data security and information privacy issues in the lodging industry: the impact of brand confidence - Han, Heesup; Zhang, Chen Jason; Ketema, Abrham Fentaw; Kim, Seongseop Sam; Chua, Bee Lia; Al-Ansi, Amr (Elsevier, 2025)
Emerging AI technologies are intensifying longstanding privacy and data security challenges in the lodging sector. Thus, this study investigated how various information privacy constructs influence customers’ decisions to switch in the context of data privacy management in the lodging industry in today's AI era. Through a multi-analytic approach, the research identified that information privacy factors (awareness, knowledge, and disposition) substantially shaped privacy control. This, in turn, heightened individuals’ sensitivity to information and strengthened their willingness to share personal data. Although heightened information sensitivity negatively affected attitudes toward data sharing, it was also positively related to switching behavior, highlighting the dual-sided implications of data privacy. The study extends the traditional risk-benefit perspective of Privacy Calculus Theory by incorporating both cognitive (awareness, knowledge) and affective (disposition) constructs into privacy control. Insights from these findings can help hoteliers reconcile guests’ privacy concerns with the industry's need for customer data.